Air transport and regional development methodologies - Adler, Nicole (London : Routledge, 2020)
Air Transport and Regional Development Methodologies is one of three interconnected books related to a four-year European Cooperation in Science and Technology (COST) Action established in 2015. The action, called Air Transport and Regional Development (ATARD), aimed to promote a better understanding of how the air transport-related problems of core regions and remote regions should be addressed to enhance both economic competitiveness and social cohesion in Europe. This book discusses key methodological approaches to assessing air transport and regional development, outlining their respective strengths and weaknesses. These include input- output analysis, cost benefit analysis, computable general equilibrium models, data envelopment analysis, stochastic frontier analysis, discrete choice models and game theory. Air Transport and Regional Development Methodologies aims at becoming a major reference source on the topic, drawing from experienced researchers in the field, covering the diverse experience and knowledge of the members of the COST Action. The book will be of interest to several large groups. First, it will serve as an authoritative and comprehensive reference for academics, researchers and consultants. Second, it will advise policy- makers and government organizations at European, national and regional levels. Third, it presents invaluable insights to transport companies such as airports and airline operators. Along with the other two books (Air Transport and Regional Development Policies and Air Transport and Regional Development Case Studies), it fills a much-needed gap in the literature.
OCLC-licensed vendor bibliographic record.
Keywords: Aeronautics, Commercial -- Social aspects -- Europe; Aeronautics, Commercial -- Economic aspects -- Europe; Regional planning -- Europe; TRANSPORTATION / Aviation / Commercial; BUSINESS & ECONOMICS / Industries / Transportation